2020
DOI: 10.24198/pacnj.v1i2.28846
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CPR Position (Kneeling, Footstool and Standing Beside Bed) on Cardiopulmonary Resuscitation Quality: A Literature Review

Abstract: Background: Cardiopulmonary Resuscitation (CPR) is one of the measures to deal with emergency cardiac arrest (cardiac arrest) where the heart organ loses its function suddenly. Hence it is unable to pump blood throughout the body. CPR consists of aid in circulation (compression) and breathing (ventilation). AHA has determined guidelines for implementing CPR, especially an essential point in CPR, namely chest compression. The standing position is fundamental in the implementation of CPR, but kneeling and footst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…However, the SS method has some limitations in fully recoiling. As in the previous study, it is unclear whether this was due to an incomplete recoil; we suspect it was caused by an unstable position 13,14 . Also, our study found no statistically significant difference in adequate chest compression depth (percentage).…”
Section: Discussionmentioning
confidence: 62%
“…However, the SS method has some limitations in fully recoiling. As in the previous study, it is unclear whether this was due to an incomplete recoil; we suspect it was caused by an unstable position 13,14 . Also, our study found no statistically significant difference in adequate chest compression depth (percentage).…”
Section: Discussionmentioning
confidence: 62%